Biology of Selected Opiine Parasitoids (Braconidae) and Their Abundance Relative to the Host Bactrocera Dorsalis (Hendel). on Carambola - Palacio, Isabelo Del Pilar (1991)
The apiines (Hymenoptera : Braconidae) are important parasitoids of the oriental truit fly. Bactrocera dorsalis (Hendel) (Diptera : Tephritidae). In an attempt to exploit their potential in the integrated control of this pest. field and laboratory studies were conducted to generate information about the biology and abundance of the major species, Based on contribution to overall parasitisation. the opiine parasitoids associated with B. dorsalis in star fruit can be arranged in the following order of importance : Biosteres persulcatus Silvestri, 46.53% B. arisanus (Sonan), 32.82% B. lonqicaudatus Ashmead, 5.69% Opius fletcheri Silvestn, 4.95%. field populations of fruit fly and parasitoids had two peak periods yearly, and both were significantly correlated with abundance of their respective host, except B. lonqicaudatus. However, their activities were significantly unaffected by size and height of host fruit in the tree.